2021
DOI: 10.1186/s12870-021-03376-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome and metabolome analysis reveal glutathione metabolic network and functional genes underlying blue and red-light mediation in maize seedling leaf

Abstract: Background Light quality severely affects biosynthesis and metabolism-associated process of glutathione. However, the role of specific light is still unclear on the glutathione metabolism. In this article, comparatively transcriptome and metabolome methods are used to fully understand the blue and red-light conditions working on the glutathione metabolism in maize seedling leaf. Results There are 20 differently expressed genes and 4 differently exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Numerous studies have shown that the responses of antioxidants vary with the proportion of red and blue light, plant species, their genotypes and development stages (Choi et al, 2013;Manivannan et al, 2017;Ye et al, 2017;Yu et al, 2017;Liu et al, 2018). In our study, WB (B:G:R = 70:21:9) increased the contents of GSH and ASA (Figure 5), which may be due to blue light changes transcription signal transduction and metabolism of GSH and ASA metabolism (Liu and Zhang, 2021). WB also enhanced activities of antioxidant enzymes (SOD, POD, CAT, and APX) in leaves or stems of wheat seedlings (Figure 6), which is similar to the results reported by Kook et al (2013), who found blue LEDs light improved CAT and APX activities of lettuce.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous studies have shown that the responses of antioxidants vary with the proportion of red and blue light, plant species, their genotypes and development stages (Choi et al, 2013;Manivannan et al, 2017;Ye et al, 2017;Yu et al, 2017;Liu et al, 2018). In our study, WB (B:G:R = 70:21:9) increased the contents of GSH and ASA (Figure 5), which may be due to blue light changes transcription signal transduction and metabolism of GSH and ASA metabolism (Liu and Zhang, 2021). WB also enhanced activities of antioxidant enzymes (SOD, POD, CAT, and APX) in leaves or stems of wheat seedlings (Figure 6), which is similar to the results reported by Kook et al (2013), who found blue LEDs light improved CAT and APX activities of lettuce.…”
Section: Discussionsupporting
confidence: 54%
“…Supplementary BL did not affect the amount of GSH, whereas supplementary FRL even decreased it compared to WL in wheat, and both spectral modifications reduced the transcription of the glutathione synthase gene [ 67 ]. The transcriptional regulation of the genes of GSH-metabolism by spectrum was also confirmed in maize, in which BL had a stronger effect on their expression compared to RL [ 169 ]. GSH, due to its central position in the redox system, may mediate the effect of the light spectrum on many metabolic processes, but the clarification of these regulatory mechanisms needs further investigations.…”
Section: Light Intensity- and Spectrum-associated Adjustment Of Metab...mentioning
confidence: 98%
“…Comparative transcriptome analysis can be used to identify essential genes involved in specific metabolic pathways ( Liu and Zhang 2021a , 2021b ). In this study, four unidentified genes were found in six comparisons between light treatments.…”
Section: Discussionmentioning
confidence: 99%